HUBUNGAN PERSONAL HYGIENE DAN KEPADATAN HUNIAN KAMAR DENGAN KEJADIAN SKABIES PADA SANTRI DI PONDOK PESANTREN PERADABAN AL-AMIN PAMEUNGPEUK GARUT TAHUN 2026 - Eti Rohayati (Bajang Institute, 2026)
Introduction: Skabies is an infectious skin disease that is still a health problem in the Islamic boarding school environment due to the high interaction between students, the use of facilities together, and the conditions of the dense residential environment. Behavioral factors such as personal hygiene and environmental factors such as housing density are known to play a role in increasing the risk of transmission of Sarcoptes scabiei. This condition makes pesantren one of the environments that is vulnerable to the occurrence of scabies. Objective: This study aims to analyze the relationship between personal hygiene and room occupancy density with the incidence of scabies in students of the Al-Amin Pameungpeuk Garut Civilization Islamic Boarding School. Methods: This study used a quantitative design with a cross-sectional approach. The research population is all students of the Al-Amin Pameungpeuk Garut Islamic Boarding School. The research sample amounted to 74 respondents using simple random sampling techniques. Data were collected using personal hygiene questionnaires, scabies incidence questionnaires, and room occupancy observation sheets. Results: The results showed that most of the respondents had poor personal hygiene (75.7%), lived in a crowded room (85.1%), and experienced scabies (55.4%). Bivariate analysis showed that there was a significant relationship between personal hygiene and the incidence of scabies (p-value = 0.000) and a significant relationship between room occupancy density and the incidence of scabies (p-value = 0.000). Conclusion: Personal hygiene and room occupancy density are significantly related to the incidence of scabies in students. This finding emphasizes the importance of the efforts of the Al-Amin Civilization Islamic Boarding School to carry out promotive and preventive measures through improving personal hygiene behavior, managing residential density according to environmental health standards, periodic health checks, and strengthening the Islamic Boarding School Health Post (Poskestren) to reduce the incidence of scabies in the pesantren environment and the efforts of students to maintain good personal hygiene